2019
DOI: 10.1177/000313481908500434
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Surgery for Benign and Low-Grade Malignant Diseases of the Duodenum

Abstract: Robotic duodenal surgery (RDS) is a treatment option for many benign and low-grade malignant duodenal conditions that are not amenable to endoscopic intervention and can avoid morbidity related to open surgery. A retrospective review of all patients undergoing RDS (non-Whipple) at a tertiary care center from 2010–2017 was carried out. Indications, procedural details, and outcomes were reviewed. Twenty-four patients underwent RDS during the study period: transduodenal resection in 6 patients (25%), wedge resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…A robotic approach may overcome many of the technical challenges associated with a laparoscopic approach while maintaining the advantages of minimally invasive surgery. [21][22][23][24][25] For example, the robotic platform allows fine suture/small needle use, [17][18][19][20][21][22] and the wristed instruments provide additional degrees of freedom to facilitate suturing and a complete sweep of the biliary tree to remove stones/sludge. 22 Similarly, the ability to efficiently suture the enterotomy from the previous anastomosis precludes the need for stapling to preserve Roux length, while minimizing mobilization and undue tension on the new anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A robotic approach may overcome many of the technical challenges associated with a laparoscopic approach while maintaining the advantages of minimally invasive surgery. [21][22][23][24][25] For example, the robotic platform allows fine suture/small needle use, [17][18][19][20][21][22] and the wristed instruments provide additional degrees of freedom to facilitate suturing and a complete sweep of the biliary tree to remove stones/sludge. 22 Similarly, the ability to efficiently suture the enterotomy from the previous anastomosis precludes the need for stapling to preserve Roux length, while minimizing mobilization and undue tension on the new anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Literature related to complex surgical procedures performed using a robotic surgical platform suggest potential technical advantages for revision of biliary strictures. [17][18][19][20][21][22] In this study, we detail our technical approach to robotassisted revision of strictured biliary anastomoses and report outcomes related to its implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, identification of the location of the tumour and the appropriate resection line from the serosal surface is challenging. Recent studies have shown that robotic surgical systems could be helpful for intricate manipulations of duodenal pathologies 6,29,30 . Our team also previously introduced a technique for robotic transduodenal ampullectomy 7 .…”
Section: Discussionmentioning
confidence: 99%
“…However surgical systems could be helpful for intricate manipulations of duodenal pathologies. 6,29,30 Our team also previously introduced a technique for robotic transduodenal ampullectomy. 7 The unique feature of our technique is the patient's left semilateral positioning for efficient exposure of duodenal lesions.…”
Section: F I G U R Ementioning
confidence: 99%
“…Neben der klassischen offenen Ampullektomie mehren sich derzeit die Fallberichte zu laparoskopischen oder ro- botergestützten Operationen [29,30]. Dabei ist das prinzipielle Vorgehen unverändert (Box OP-Schritte und Tricks).…”
Section: Transduodenale Ampullektomieunclassified